Business Model Formulation For Yarn Store As Cultural Tourism: A Case Study of Mondu Crafts - Widodo, Ameera Rahil Sahira; Chaldun, Evy Rachmawati (Integrasi Sains Media, 2024)
This study aims to develop a sustainable business model for the first physical store of Mondu Crafts, a yarn store targeting cultural tourism. Research objectives include analyzing market characteristics, identifying factors affecting the business, and designing a suitable strategy. A mixed-method approach was used, employing questionnaires and interviews, analyzed through descriptive and cross-tabulation methods. Key findings indicate strong interest in Mondu Crafts, especially among females aged 17-35. High-income groups face time constraints, while lower-income groups face budget limitations. Strategies such as offering free, short trial workshops are recommended. Results highlight the trend for one-stop shops, integrating sightseeing, food, activities, and souvenirs. Long-term sustainability suggestions include integrating AI-based language translation services and eco-friendly initiatives. Establishing Mondu Crafts Cafe & Store in Bandung is both market-viable and financially feasible, with potential expansion to Bali for a broader reach. The study provides practical insights for developing a robust Business Model Canvas for a creative economy as a cultural tourism.